Interleukin-4 receptor alpha gene variants and allergic disease - Hall, Ian P. (2000)
The interleukin-4 (IL-4) signalling cascade has been identified as a pathway potentially important in the development of asthma. Genetic variants within this signalling pathway might contribute to the risk of developing asthma in a given individual. A number of polymorphisms have been described within the IL-4 receptor alpha (IL-4Ralpha) gene. In addition polymorphism occurs in the promoter for the IL-4 gene itself. This commentary accompanies a paper by C Ober et al describing the contribution of IL-4Ralpha polymorphism to susceptibility to asthma and atopy in the Hutterite population and other outbred populations collected during the collaborative studies on the genetics of asthma (CSGA) programme